2018
DOI: 10.1016/j.juro.2017.08.076
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Partial Gland Ablation and Radical Prostatectomy to Treat Low and Intermediate Risk Prostate Cancer: Oncologic and Functional Outcomes

Abstract: In select patients with organ confined prostate cancer partial gland ablation offered good oncologic control with fewer adverse effects that required additional treatments. Potency and continence appeared to be better preserved after partial gland ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…FT is delivered by a variety of energy modalities including: photothermal ablation, high‐intensity focussed ultrasound (HIFU), and cryotherapy, amongst others . FT has been shown to have acceptable early term disease‐free control rates in well‐selected patients .…”
Section: Introductionmentioning
confidence: 99%
“…FT is delivered by a variety of energy modalities including: photothermal ablation, high‐intensity focussed ultrasound (HIFU), and cryotherapy, amongst others . FT has been shown to have acceptable early term disease‐free control rates in well‐selected patients .…”
Section: Introductionmentioning
confidence: 99%
“…A comparative analysis has looked into oncological and functional outcomes of partial gland ablation (PGA) vs. RARP and showed that PGA renders better preservation of continence and potency after a mean follow-up of 38 months. However, these improved outcomes came at the cost of a higher rate of treatment failures and the need for salvage therapy after PGA 27 .…”
mentioning
confidence: 99%
“…The results of the SMRW cohort supported the validity of the results. Garcia-Barreras et al (10) also reported an inferior efficacy of CA. They compared the oncological outcomes between 236 partial gland CA patients and 472 matched robot-assisted RP patients.…”
Section: Discussionmentioning
confidence: 97%
“…Some single-arm case series showed that CA has a favorable short-intermediate term oncological efficacy in patients with clinically low-intermediate risk PCa (8,9). Furthermore, other studies comparing radical prostatectomy (RP) and CA reported comparable oncological outcomes between the two interventions (10,11). However, given the lack of comparative study of CA vs. RP with mid-long followup period, significant uncertainties remain in considering CA as an alternative strategy to radical prostatectomy (RP) for localized PCa.…”
Section: Introductionmentioning
confidence: 99%